Melampaui Positivisme: Krisis Relevansi Epistemologis Penelitian Manajemen Pendidikan Tinggi dan Transformasi Universitas Berbasis Inovasi Sumber Daya Alam Lokal Untuk Pembangunan Sdm Unggul Indonesia 2045 - Dany Rakca (LPPM Institut Pendidikan Nusantara Global, 2026)
Research on higher education management in Indonesia has largely been built upon a positivist paradigm that emphasizes measurability, generalization, and methodological rigor. While this approach has contributed to strengthening academic governance, its relevance is increasingly questioned as universities are expected to play a more active role in socio-economic transformation and the development of high-quality human resources. This article examines the epistemological relevance crisis of the positivist paradigm and proposes a reorientation of higher education management research toward more contextual and transformative approaches. Using a conceptual-critical perspective, the article demonstrates that the dominance of positivism tends to confine the role of universities to that of graduate producers, thereby neglecting their strategic capacity as centers of innovation and creators of economic value based on local natural resource potential. The conceptual findings of this article underscore that the adoption of post-positivist and transformative research paradigms is a prerequisite for strengthening university contributions to the agenda of independent natural resource governance, as articulated in the 2024–2029 Asta Cita Government Program. Consequently, reorienting the research paradigm of higher education management constitutes a crucial foundation for human capital development and the strengthening of nation-building efforts toward Indonesia Emas 2045.